Correlation between motor impairment and participation in children with cerebral palsy - Diwan, Shraddha J.; Rathod, Neelam K.; Ganatra, Hiral; Vyas, Neeta (International Journal of Contemporary Pediatrics, 2017)
Background: Children with chronic functional limitations have considerably more difficulties in the social and behavioral aspects of their lives than typical children. In CP, dysfunction of muscle control prevails, which can lead to spasticity or shifting muscle tone, to associated pathological postures, and to decreased range of joint motions. Activity limitations refer to difficulties in executing tasks or actions which focused on limitations in mobility, addressing walking, lifting and arm/hand use, and in self-care activities. Few studies are available which measure the participation and impairments. But there is also need to evaluate participation in relation to impairments. So, the purpose of the current study is to find out the co- relation between motor impairment and participation in children with cerebral palsy. Methods: Convenient sample of 20 children with CP were selected according to selection criteria i.e. diagnosed case of CP with age 5 years or more and children with conditions like autism spectrum disorder, attention deficit hyperactive disorder, Down’s syndrome, spina bifida, metabolic disorders, and traumatic brain injuries were excluded. GMFCS and PEDI were taken in each of them. Statistical analysis was done. Results: The result showed negative correlation between GMFCS level and different domains of PEDI: self-care, mobility and social function using spearman’s correlation with r: -0.77, -0.82, -0.78. Conclusion: Children with lower level of GMFCS had higher participation while those with higher level of GMFCS had lower participation. So, participation is depends up on motor impairments.